A MODEL FOR MEDICAL DIAGNOSTIC LABORATORY: MULTIMEDIA DATABASE APPROACH - D. V. Tuyet; S. V. Ablameyko (Informatika)
There are two main tendencies in Medical Informatics. One is the development of core theory in the information technology itself and the other one is the use of technologies in applications for health improvement. In recent years, the deployment of Health Information Technology (HIS) applications and Laboratory Information System (LIS) in some big hospitals have enhanced the quality of administrative management and actively supported the diagnosis and treatment tasks of the physician. In this paper, we will present an architectural model of the Medical Diagnostic Laboratory (MDL).